Tingkat Pengetahuan Pelajar SMK N 1 Bancak Kabupaten Semarang terhadap Kesehatan Reproduksi Remaja (KRR) - Sanfia Tesabela Messakh; Esterrina Prihastuti; Bagus Panuntun Sukma Adi (Journal of Health (JoH), 2019)
Reproductive health education is not commonly talked about in Indonesian communities since it is still considered taboo. This result in the lack of understanding of a good basic knowledge of reproductive health, especially among the teenager. The lack of understanding makes the teenagers become quite fragile to negative behavior such as premarital sex which might resulted in unwanted pregnancy, abortus or even sexually transmitted diseases. The aim of this study is to describe the level of knowledge on reproductive health among the students of State Vocational High School in Bancak. The results showed that the respondents with sufficient knowledge as much as of 51.9%, as much good knowledge to 40.5%, and less knowledge as much as of 7.6%. Based on the result of the research, it can be concluded that the level of knowledge of State Vocational High School in Bancak on Adolescent Reproductive Health is in the category of medium.